Modeling direct above-ground carbon loss due to urban expansion in Zanzibar City Region, Tanzania - Kukkonen Markus O.; Khamis Miza; Muhammad Muhammad J.; Käyhkö Niina; Luoto Miska (Elsevier Ltd, 2022)
Expansion of urban fabric on carbon storages is estimated to cause loss of 1.38 Pg of Above-Ground Carbon (AGC) in pan-tropics between 2000 and 2030. This would be approximately 5% of all emissions caused by tropical land use changes. Despite the significance of the phenomenon, these emissions are rarely measured, monitored, or addressed in climate change mitigation plans, especially in Sub-Saharan Africa. Therefore, we demonstrated a state-of-the-art approach predicting AGC loss of Zanzibar City Region under multiple alternative urban planning scenarios between 2013 and 2030. The AGC information was modeled based on field measured forest inventory sample plots and RapidEye satellite data from 2013, while the future urban expansion model was calibrated with data of happened expansion between 2004, 2009 and 2013, and geospatial independent variables influencing the expansion patterns. This model was then projected until 2030, while alternative urban planning scenarios were integrated to the model by modifying the geospatial variables. The combination of these two models indicates that 42,000 Mg or 15% of total AGC in Zanzibar City Region can be anticipated to be lost by 2030 due to urban expansion. Majority of the loss will take place in the agroforest and fruit tree plantations surrounding the city, while natural forest face limited impacts. None of the tested alternative urban planning scenarios significantly impact the loss of AGC compared to the business-as-usual scenario. Therefore, alternative policies and plans are seriously needed to address the issue in Zanzibar. These could include promoting urban densification, directing urban expansion to low carbon areas, improving soil carbon management, and preparing an urban forestry and greenery strategy. All in all, the study indicates that data and methods are available for monitoring and predicting the phenomenon in Sub-Saharan Africa. Research based on a comparable methodology should be produced from all the main cities in the region that are surrounded by significant carbon storages and facing high urban expansion rates to support climate change mitigation.